Developing a woman-centered, inclusive definition of traumatic childbirth experiences: A discussion paper - Leinweber, Julia; Fontein-Kuipers, Yvonne; Thomson, Gill; Karlsdóttir, Sigfrídur Inga; Nilsson, Christina; Ekström-Bergström, Anette; Olza, Ibone; Hadjigeorgiou, Eleni; Stramrood, Claire (My University, 2022)
Many women experience giving birth as traumatic. Although women's subjective experiences of trauma are considered the most important, currently there is no clear inclusive definition of a traumatic birth to help guide practice, education, and research.
Keywords: obstetric violence; post-traumatic stress disorder; postpartum; subjective; traumatic childbirth